Anesthesia for Same Day Discharge After Craniotomy: Review of a Single Center Experience. Issue 4 (October 2018) - Sheshadri, Veena; Venkatraghavan, Lashmi; Manninen, Pirjo; Bernstein, Mark
Abstract : Same day discharge or outpatient surgery for intracranial procedures has become possible with the advent of image-guided minimally invasive approaches to surgery and availability of short-acting anesthetic agents. In addition, patient satisfaction and the benefits of avoiding hospital stay have resulted in the evolution of neurosurgical day surgery. We reviewed our experience and the available literature to determine the perioperative factors involved which have promoted and will improve this concept in the future. Craniotomy and biopsy for supratentorial brain tumors and surgical clipping of intact cerebral aneurysms have been successfully performed as day surgeries. Patient perceptions and satisfaction surveys have helped in better understanding and delivery of care and successful outcomes. There are major differences in health care across the globe along with socioeconomic, medicolegal, and ethical disparities, which must be considered before widespread application of this approach. Nevertheless, collaborative effort by surgeons, anesthesiologists, and nurses can help in same day discharge of patients after cranial neurosurgery.